Exploring the successful factors of homestay entrepreneurs in Kampong Sungai Haji Dorani, Selangor - Nursyamira Mohd Nor; Nurul Afifah Asraf Ali; Priskila Jaimi; Siddique Nain Zulkarnain (2016)
The purpose of this study is to determined and discover the challenges that homestay entrepreneurs faces in order to expand their business in tourism industry, by interviewing and collecting the data about the homestay entrepreneurs and his/her background. In addition, this study also want to identify the factors that influenced the development of homestay whether luxury hotel and budget hotel give a big impact to the homestay industries by interviewing the correspondent which is the homestay entrepreneurs by determine how long he/she have being in the homestay industry. Next is to investigate the relationship between the barriers and challenges which stand as the independent variables. To understand the relationship between the barriers and the challenges that been faces by the homestay entrepreneurs in order to develop the business, this study have accept qualitative research methodology to examine the result of the hypotheses. In this case, many regressions have been used to find the relationships between the independent variables (factors) and factors that affect the development of the homestay in the tourism industry. Several interview session will be held between the homestay entrepreneurs and tourists to get their opinion and this opinion will be analyse to determine the factors that affect the variable.